Pyroligneous Acids of Differently Pretreated Hybrid Aspen Biomass: Herbicide and Fungicide Performance - Korkalo, Pasi; Hagner, Marleena; Jänis, Janne; Mäkinen, Marko; Kaseva, Janne; Lassi, Ulla; Rasa, Kimmo; Jyske, Tuula (Frontiers in Chemistry, 2022)
The pyroligneous acids (PAs) of woody biomass produced by torrefaction have pesticidal properties. Thus, PAs are potential alternatives to synthetic plant protection chemicals. Although woody biomass is a renewable feedstock, its use must be efficient. The efficiency of biomass utilization can be improved by applying a cascading use principle. This study is novel because we evaluate for the first time the pesticidal potential of PAs derived from the bark of hybrid aspen (Populus tremula L. × Populus tremuloides Michx.) and examine simultaneously how the production of the PAs can be interlinked with the cascade processing of hybrid aspen biomass. Hybrid aspen bark contains valuable extractives that can be separated before the hemicellulose is thermochemically converted into plant protection chemicals. We developed a cascade processing scheme, where these extractives were first extracted from the bark with hot water (HWE) or with hot water and alkaline alcohol (HWE+AAE) prior to their conversion into PAs by torrefaction. The herbicidal performance of PAs was tested using Brassica rapa as the test species, and the fungicidal performance was proven using Fusarium culmorum. The pesticidal activities were compared to those of the PAs of debarked wood and of commercial pesticides. According to the results, extractives can be separated from the bark without overtly diminishing the weed and fungal growth inhibitor performance of the produced PAs. The HWE of the bark before its conversion into PAs appeared to have an enhancing effect on the herbicidal activity. In contrast, HWE+AAE lowered the growth inhibition performance of PAs against both the weeds and fungi. This study shows that hybrid aspen is a viable feedstock for the production of herbicidal and fungicidal active chemicals, and it is possible to utilize biomass according to the cascading use principle.